Advancing Sustainability of Primary Healthcare Services: A Multiple Case Study of Donor-Funded Non-Communicable Disease Programmes - Stanton,Louise Nathalie (2026)
The unprecedented decline in external health aid has disrupted health services across low- and middle-income countries, many of which are simultaneously facing rising levels of non-communicable diseases and weak primary healthcare, increasing the need to examine how donor-driven non-communicable disease programmes can be sustained beyond programme completion. This thesis unfolds how sustainability of such programmes can be achieved, by drawing on new institutional theory and the concept of institutional work to elicit how development actors shape institutional arrangements across healthcare system levels to enhance programme sustainability. A multiple case study design was employed to examine three programmes funded by the World Diabetes Foundation in Georgia, Jordan and Timor-Leste, which were selected through purposeful sampling. The study drew on qualitative data sources, including semi-structured interviews and programme documents. A within-case thematic analysis was performed, followed by a cross-case analysis in which findings were compared across cases. The study demonstrated that sustainability was fostered, when programme activities were integrated into institutional structures transcending levels of the national healthcare system. Moreover, findings showed that sustainability was strengthened when programmes built on existing national service delivery arrangements.
Keywords: Sustainability; global health programmes; non-communicable diseases; primary healthcare; institutional work; new institutionalism; multiple case study; low- and middle-income countries